From Displicent Villarrealinos To Rebel Villarrealinos: Recovering The Public University (2013-2016) - Liendo Moscoso, Alvaro (2020)
In 2014, the university reform law N ° 30220 was approved by the Congress of the Republic of Peru; in a convulsed context of opposition to the new supra-institutional parameters, which the university power groups believed, violated their autonomy. The Villarrealino student movement, with its limitations and tensions, assumed leadership in the capital during this period. Under a structure of liberalization of the educational market and demobilization inherited from the nineties, we ask ourselves: what scope and limitations did the collective action of the student movement in Villarreal present during the years 2013 to 2016? The objective of this article then will be to approximate and determine it. For this work we apply participant research and retrospective systematization of the facts as research methods; in order to reconstruct the experience and guide interventions of the movement. For this we have analyzed written and oral sources of the students and graduates involved. On the other hand, this is an essay to analyze the nuances between the various theoretical approaches of social movements, as eventually contradictory paths, applied to this case and focused on immersing oneself in the political subjectivity of those who seek change. This process of gradual conquests of the students should serve to redirect their efforts towards the university government with the same tenacity that they have destined for the grassroots organization with the ultimate aim of breaking the hegemony of the hidden party interests made visible in times of crisis; promoting legislative initiatives and providing them with mechanisms of greater democratic scope.